Debt Financing and Firm Valuation of Quoted Non-Financial Firms in Nigeria Stock Exchange - Patricia Oranefo; Chinedu Egbunike (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study examined the effect of debt financing on the firm valuation of quoted non-financial firms on the Nigerian Stock Exchange (NSE). The study specifically evaluated the effect of short-term debt to equity, long-term debt to equity, and total debt to assets on Tobin’s Q for the period 2011 to 2019. Methodology: The study adopts the ex post facto research design. The sampling technique utilized in the study was non-probability sampling. The final sample comprised seventy-five firms quoted non-financial firms on the Nigerian Stock Exchange (NSE). The secondary data obtained from MachameRATIOS®were analyzed using panel regression techniques. Unlike prior studies, the study also employs the Arellano Bond Dynamic Panel-data Estimation Model for robustness analysis. Results: There is a negative effect of short-term debt to equity on Tobin’s Q. The effect of long-term debt to equity and total debt to assets was positive and significant. Limitations: The main limitation is the unbalanced nature of some sectors due to data unavailability. Contribution: The study contributes to the literature in the context of developing countries, on the effect of long-term debt on firm valuation; consistent with the trade-off theory of the cost of long-term debt financing as an alternative to internal funding.